PROBLEMATIKA EKONOMI SEBAGAI ALASAN UTAMA PERCERAIAN DI PENGADILAN AGAMA KABUPATEN BANYUWANGI - Luk Luk Khoirurrizalina; Witia Oktaviani (USRAH: Jurnal Hukum Keluarga Islam, 2025)
In 2024, Banyuwangi Regency ranked third in highest divorce cases due to economic factors in East Java, despite regional economic growth increasing by 4.68%. This phenomenon has become a significant concern in Islamic family law. This study analyzes types of economic problems influencing divorce, economic reasons as basis for judges' consideration in granting divorce, and efforts of Banyuwangi Regency Religious Court to protect women's and children's rights in divorce cases due to economic factors. Using descriptive qualitative method with in-depth interview techniques with Panel of Judges and analysis of divorce decisions and statistical data. Findings indicate economic factors are not primary causes of divorce, but triggers for recurring household disputes.Types of economic problems include unemployed husbands, insufficient household income, and husbands completely failing to provide financial support. Panel of Judges considers impacts of economic conflicts on relationship breakdown such as broken marriage, emotional distress, and absence of willingness to repair relationships. Wives are entitled to receive iddah maintenance, mut'ah compensation, and madhiyah support without evidence of nusyuz behavior. Husbands must pay maintenance before judges decide on divorce. Child custody rights are granted to mothers if children are under 12 years old, while children above 12 years old may choose between both parents. Keywords: Divorce; Economic Issues; Livelihood; Islamic Court.